Effectiveness of water fluoridation in the prevention of dental caries across adult age groups. Issue 3 (16th January 2017) - Do, Loc; Ha, Diep; Peres, Marco A.; Skinner, John; Byun, Roy; Spencer, A. John
Abstract: Background: Lifetime access to fluoridated water (FW) is associated with lower caries experience. However, assessing this association in adults is likely affected by age. Cohort stratification and categorization of per cent lifetime access to fluoridated water (% LAFW) within cohorts are current approaches to this assessment. These approaches require an examination of the % LAFW and caries experience variation within and across age groups and their association to inform future analyses. Objective: This secondary analysis aimed to examine the age group variation in % LAFW and caries experience; and the association of % LAFW with caries within and across age groups of adults. Methods: A secondary analysis was undertaken using the Australian National Survey of Adult Oral Health 2004‐2006 data on 4090 persons aged 15‐91 years randomly sampled by a stratified, multistage probability method. Study participants underwent an interview, an oral examination by trained and standardized dentists to determine decayed, missing or filled tooth surfaces (DMFS) and a mailed self‐complete questionnaire which collected residential history to calculate % LAFW. Variations in % LAFW and DMFS across age groups (15‐34; 35‐44; 45‐54; 55+) were examined. Multivariable regression log‐link models were generated for DMFS score within each age group. Results: The age groups varied in values and distribution of % LAFW. Caries experience was strongly associated with age. % LAFW was significantly associated with DMFS score in the two younger age groups, but not in the others. Multivariable regression models showed that the highest % LAFW quartile had significantly lower DMFS count than the lowest quartile in the two younger age groups (mean ratios: 0.67 and 0.78, respectively), controlling for other covariates. Conclusion: Access to FW was associated with caries experience in Australian adults. The magnitude of associations varied between age groups, dependent on the natural history of caries and its measurement by DMFS.